Status index of optimal water variables for biodiversity conservation in the Lagoon of Sonso in Colombia - Gloria Yaneth Florez-Yepes; Alejandro Rincón; Vladimir Henao Céspedes; Juan Carlos Granobles Tores; Fredy Edimer Hoyos Velasco (Institute of Advanced Engineering and Science, 2022)
In order to determine an index of the status of optimal water variables for biodiversity conservation in the Sonso Lagoon, the data obtained from 2004 to 2018 were used. To determine the index, a methodology based on a multivariate analysis of the physical-chemical water variables was used, as well as a correlation analysis for their delimitation. Subsequently, the definition of weights and the parameterization of the variables for the final construction of the index were made. As a result, it was found that the lagoon is in an adequate state with a value index of 0.65, with a highly vulnerable tendency to be in an acceptable state and go to a critical state, depending on the anthropic pressure it has. As a conclusion, it was obtained that variables such as dissolved oxygen, total phosphorus and electrical conductivity are determining factors in establishing the index.